Monte Carlo simulations of an innovative molecular breast imaging system for the small breast cancer diagnosis using GATE. Issue 11 (2nd December 2019) - Poma, G. E.; Garibaldi, F.; Giuliani, F.; Insero, T.; Lucentini, M.; Marcucci, A.; Musico, P.; Petta, C.; Santavenere, F.; Sutera, C.; Cisbani, E.
ABSTRACT: This paper draws attention to the study of performance of a new Molecular Breast Imaging (MBI) device, whose purpose is the early diagnosis of breast cancer, using Monte Carlo simulations. MBI provides functional and specific information that are more appropriated to dense breasts. Two asymmetric heads with different types of collimators, facing each other in anti-parallel viewing direction, characterize the system. Detectors and phantoms, together with the data taking procedure, are shortly reported. Monte Carlo simulations using the GATE (GEANT4 Application for Tomographic Emission) simulation toolkit have been implemented to evaluate the optimal detector configuration, in terms of sensitivity and spatial resolution, and also to reproduce the real experimental data. The device can be used both in spot compression and in Limited Angle Tomography (LAT); in the latter configuration one detector head with pinhole collimator is able to rotate around the breast in order to diagnose and localized the small tumors.